Anodal tDCS and virtual reality gait rehabilitation in individuals with chronic stroke: a case series report - Marks, Aracely; Oliveira Barbosa, Shelley; Napoli, Daniella; D'Andrea, Susan E. (Frontiers in Stroke, 2025)
BackgroundStroke is a principal cause of long-term disability worldwide, significantly impairing motor function, including gait and mobility. Conventional physical therapy, primarily focusing on repetitive, task-specific exercises, often falls short in addressing the complex rehabilitative needs of stroke survivors. Emerging technologies such as virtual reality (VR) and transcranial direct current stimulation (tDCS) have shown potential to enhance neuroplasticity and functional recovery, suggesting that their combined use could offer a novel pathway for stroke rehabilitation.ObjectiveThis study evaluated the efficacy of an integrated VR and tDCS treadmill training protocol in improving gait and mobility outcomes among individuals with chronic stroke.MethodsFive chronic stroke patients were recruited for this study. Participants were randomly assigned to receive either anodal tDCS or sham stimulation in conjunction with VR treadmill training. The anodal stimulation was targeted at the ipsilesional motor cortex, specifically over the primary motor cortex (M1) area corresponding to the C3/C4 locations in the 10–20 EEG system. The intervention consisted of 10 30-min sessions over 2 weeks. Clinical assessments, including the Dynamic Gait Index (DGI), Berg Balance Scale (BBS), 10-meter Walk Test (10MWT), and the Timed Up and Go Test (TUG) were conducted pre-intervention, immediately post-intervention, and at a 2-week follow-up.ResultsAll participants demonstrated improvements in the clinical measures post-intervention, irrespective of whether they received anodal tDCS or sham stimulation. Notably, clinically significant improvements, defined by an improvement greater or equal to the established minimal clinically important differences (MCIDs), were observed in DGI scores for four participants, suggesting enhanced gait functionality.ConclusionThe combined VR and tDCS interventions promise to improve gait and mobility in chronic stroke survivors. While the observed improvements were not distinctly attributed to tDCS, the role of VR training was notably beneficial. These preliminary findings underscore the potential of integrating emerging technologies in stroke rehabilitation and highlight the need for future research with larger cohorts to explore the distinct contributions of each modality and validate this integrative approach.